2009
DOI: 10.1111/j.1551-2916.2009.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of La on Dielectric and Piezoelectric Properties of Pb1−xLa2x/3(Nb0.95Ti0.0625)2 O6 Ceramics

Abstract: Ceramics with the chemical compositions of Pb1−xLa2x/3(Nb0.95Ti0.0625)2O6 (0≤x≤0.060) (PLTN) were prepared by the conventional solid‐state reaction method. X‐ray diffraction analysis indicated that Ti and La doping not only decreased the rhombohedral–tetragonal phase transformation temperature, but also stabilized the orthorhombic phase of PLTN ceramics. All ceramics sintered at 1190°–1250°C had shown the pure orthorhombic ferroelectric phase. La doping suppresses grain growth and inhibits the formation of por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Figure 8 shows the P – E hysteresis loops of the PBNT ceramic sintered at 1260°C. Although saturation has not been reached, the loops are similar to those of other PN‐based ceramics with a single orthorhombic ferroelectric phase reported previously 3,11 …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 8 shows the P – E hysteresis loops of the PBNT ceramic sintered at 1260°C. Although saturation has not been reached, the loops are similar to those of other PN‐based ceramics with a single orthorhombic ferroelectric phase reported previously 3,11 …”
Section: Resultssupporting
confidence: 82%
“…The addition of Ti could not only increase the densification of the PN ceramics but also increase the Curie temperature 9,10 . Recently, our group has studied the effects of La and Ti on the dielectric and piezoelectric properties of the PN‐based ceramics 11,12 . We found that the doping of La and Ti into the PN ceramics could enhance the density and restrain the grain growth, resulting in a high piezoelectric constant and low dielectric loss.…”
Section: Introductionmentioning
confidence: 97%
“…Third, BS–PT– x CTO shows a high resistance and a low dielectric loss mainly due to the low density of oxygen vacancies and large band gap at 20–450 °C, so the in situ d 33 , k p , k t , and Q m can be exactly measured. For comparison, Figure d shows the dependence of the room-temperature d 33 value on the ceramic T C of the well-known high-temperature piezoelectric ceramics. , The d 33 value decreases with increasing T C for most piezoelectric ceramics. As an example, the commercial PZT-5A ceramics show a d 33 of 365 pC/N at room temperature and a T C of 365 °C; however, they have a serious depolarization above 200 °C .…”
Section: Resultsmentioning
confidence: 99%
“…The Ca 2 þ , Mn 4 þ and Ti 4 þ ions were also found to facilitate the densification of the PN-based ceramics [8][9][10]. Previously, we found that the doping of La 3 þ and Ti 4 þ ions can enhance the densities of the ceramics and restrain grain growth, resulting in high-piezoelectric constant and low dielectric loss [11]; the doping of Ti 4 þ and Ba 2 þ can also facilitate densification of the ceramics and improving dielectric and piezoelectric properties [12][13] [14]. These results demonstrate that we can obtain dense PN-based ceramics with enhanced piezoelectric properties via the conventional solid state reaction method if some appropriate dopants were added into PN.…”
Section: Introductionmentioning
confidence: 92%